Impact of Social Media on Senior Secondary School Students’ Involvement in Cybercrime in UDI Local Government Area of Enugu State, Nigeria - Judith Nneka Okafor; Helen Chibuogwu Enwezor; Obinna Nonso Anachuna; Valentina Anurika Etele; Nwamaka Florence Mokwe; Pius Okechukwu Chukwu (European Scientific Journal, ESJ, 2025)
This study investigated the impact of social media on senior secondary school students’ involvement in cybercrime in Udi Local Government Area of Enugu State, Nigeria. Two research questions guided the study, and two null hypotheses were formulated for the study and tested at a 0.05 level of significance. The study employed a descriptive survey research design. The respondents used for the study consisted of 173 SS 2 students (73 males and 100 females) from the four schools sampled for the study using a simple random sampling technique (balloting). Data was collected using the Social Media and Cybercrime Questionnaire (SMCQ), which was validated by experts. An estimate of the stability of the instrument yielded a reliability coefficient of 0.85 using Cronbach’s Alpha statistic. Mean and standard deviation were used as descriptive statistics to answer the research questions, while the independent samples t-test was adopted as an inferential statistic. The findings indicated that male students have a higher level of addiction to social media than their female counterparts, and male students are more involved in cybercrime as a result of social media influence than their female counterparts. The results also revealed that there is no significant difference in the mean responses of male and female students on the influence of social media on their involvement in cybercrime in secondary school. It was recommended that the school authorities should monitor both the male and female students on the usage of social media in schools, as its usage has a positive relationship with their involvement in cybercrime.